Synchronous online teaching, a blessing or a curse? Insights from EFL primary students' interaction during online English lessons. (August 2021) - Cheung, Anisa
Abstract: Recent years have witnessed a rapidly growing trend of incorporating synchronous online teaching tools into language teaching, yet the interaction patterns that unfold in online environment and its effectiveness on young learners remain underexplored. The present study narrows this research gap through closely examining the multi-modal exchanges between a veteran primary teacher and his EFL Grade 6 students during synchronous online English lessons, using a video-conferencing tool called ZOOM. 80 recordings from whole-class and small-group sessions over a four-month span were obtained and the various modes of synchronous computer-mediated communication that the teacher employed as well as spoken discourses were analyzed. The findings indicated that the teacher successfully utilized the affordances provided by ZOOM to elicit a large number of non-verbal responses and expanded verbal responses from students. The better-able students also demonstrated remarkable interactional skills during small-group sessions, as seen from their increased use of prompting and repair speech acts. Students' reticence emerged as an alarming concern, though it was alleviated by extending the wait-time. Overall, this study offers a prototype for primary teachers to base upon during synchronous online lessons, whilst also highlights the need for re-conceptualizing the constituents of classroom interactional competence (CIC). Highlights: Primary students favored non-verbal responses, such as typing in chatroom or pressing gesture buttons during online lessons. When preceded by whole-class non-verbal responses, students' verbal exchanges were extended with more elaborated answers. Students' reticence could be a pressing issue but extending the wait-time would alleviate the problem. When unsupervised in small-group sessions, better-able peers still demonstrated remarkable interactional competence.